The Relationship between Learning Methods and Problem-Solving Effectiveness in Islamic Learning - Tanjung, Hasan Basri; Aini, Zulkefli (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to analyze the relationship between the learning methods used in Islamic learning and the problem-solving effectiveness demonstrated by students. The background of this research is based on the importance of problem-solving skills in facing the challenges of complex modern life, as well as the role of Islamic learning in shaping students' character and critical thinking. The main focus of this study is to find out the extent to which certain learning methods (lectures, discussions, and contextual methods) affect students' ability to solve problems related to teaching materials and Islamic values. This study uses a quantitative approach with a survey method. The population in this study is grade XI students from three state aliyah madrassas in the city of Bandung. The sample was taken by stratified random sampling of 120 respondents. The instrument used is in the form of a closed questionnaire that has been tested for validity and reliability. The data analysis technique used multiple linear regression. The results showed that simultaneously the learning method had a significant effect on problem-solving ability (Fcal = 14.87; p < 0.001). Partially, the discussion method had the greatest influence with the value of the regression coefficient β = 0.52 (p < 0.001), followed by the contextual method β = 0.31 (p = 0.004), and the lecture method β = 0.18 (p = 0.021). An R² value of 0.63 indicates that 63% of the variation in students' problem-solving abilities can be explained by the three methods. These results confirm that an interactive learning approach, especially discussion, is more effective in improving students' critical thinking skills in Islamic learning